2020
DOI: 10.1002/ece3.6525
|View full text |Cite
|
Sign up to set email alerts
|

Climate anomalies affect annual survival rates of swifts wintering in sub‐Saharan Africa

Abstract: Several species of migratory swifts breed in the Western Palearctic, but they differ in reproductive traits and nonbreeding areas explored in Africa. We examined survival and recapture probabilities of two species of swifts by capture–mark–recapture data collected in northern Italy (Pallid Swift Apus pallidus in Carmagnola, Turin, and Common Swift Apus apus in Guiglia, Modena) in the breeding season (May–July). Apparent survival rates were relatively high (>71%), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…Because smaller birds have lower absolute resource requirements and lower cost of transport (Pennycuick 1989), they may more successfully get through such periods, as compared to larger conspecifics. This scenario may apply to the northern part of both the breeding and the wintering ranges, where cold spells (breeding) and droughts (nonbreeding) may be frequent due to extreme weather events (Boano et al 2020), but needs to be confirmed by future studies. A third scenario may be, if there is strong competition for breeding sites in the south of the breeding range, larger individuals may have a competitive advantage to occupy and defend nest sites (Lack 1956), promoting early start of breeding as compared to small individuals.…”
Section: Gradientsmentioning
confidence: 99%
“…Because smaller birds have lower absolute resource requirements and lower cost of transport (Pennycuick 1989), they may more successfully get through such periods, as compared to larger conspecifics. This scenario may apply to the northern part of both the breeding and the wintering ranges, where cold spells (breeding) and droughts (nonbreeding) may be frequent due to extreme weather events (Boano et al 2020), but needs to be confirmed by future studies. A third scenario may be, if there is strong competition for breeding sites in the south of the breeding range, larger individuals may have a competitive advantage to occupy and defend nest sites (Lack 1956), promoting early start of breeding as compared to small individuals.…”
Section: Gradientsmentioning
confidence: 99%
“…Interestingly, there was also a negative relationship between winter NAO and survival. The effects of NAO have recently been documented on survival of Palaearctic trans-Saharan migrants (Johnston et al 2016) but not in others (Boano et al 2020). We suspect that the negative association between winter NAO and the amount of precipitation and vegetation productivity in the Mediterranean and northwestern African regions (Stige et al 2006, Vicente-Serrano & Trigo 2011 partly explains this relationship.…”
Section: Relationships Between Survival and Winter Climate In Africamentioning
confidence: 83%
“…Long-distance Afro-Palaearctic migratory insectivores have suffered higher declines than other insectivores (Bowler et al 2019) and it is suspected that climatic factors in the African wintering quarters have played a crucial role in these declines (Kanyamibwa et al 1989, Zwarts et al 2012, Norman & Peach 2013, Johnston et al 2016, Boano et al 2020. However, the population ecology of several farmland birds, and the demographic and ecological processes by which they are affected by farming practices and climate change, remain poorly known (Newton 2004, Morrison et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common swifts remain airborne during non-breeding (Hedenströ m et al, 2016), enabling a highly mobile lifestyle and exploration of ephemeral food resources (Å kesson et al, 2012;Wellbrock et al, 2017;Boano et al, 2020). The timing of movements is important with respect to food availability and winds (Å kesson and Helm 2020; Wellbrock et al, 2017;Boano et al, 2020;Å kesson et al, 2016) and involves limited periods of fueling prior to autumn migration (Å kesson et al, 2012). Although these swifts spend most of their nonbreeding year on the wing, their migrations are characterized by periods of relative geographic stasis (which we will call ''stopovers'') interspersed with periods of concerted directional flight.…”
Section: Migration Phenologymentioning
confidence: 99%